2018
DOI: 10.1002/minf.201800062
|View full text |Cite
|
Sign up to set email alerts
|

Docking of Covalent Ligands: Challenges and Approaches

Abstract: Covalent ligands have recently regained considerable attention in drug discovery. The rational design of such ligands, however, is still faced with particular challenges, mostly related to the fact that covalent bond formation is a quantum mechanical phenomenon which cannot adequately be handled by the force fields or empirical approaches typically used for noncovalent protein-ligand interactions. Although the necessity for quantum chemical approaches is clear, they cannot yet routinely be applied on large dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 93 publications
(103 reference statements)
0
48
0
Order By: Relevance
“…( Gentile et al, 2020 ; Ngo et al, 2020 ) A strategy of achieving irreversible inhibition of this protease has also been addressed by the design of compounds to create a covalent bond with the cysteine 145 residue (Cys145) of the catalytic dyad. (Pillaiyar, et al, 2020) While classical docking studies are widely reported in the literature,( Kitchen et al, 2004 ) docking studies for covalent protein inhibition are less common,( Kumalo et al, 2015 ; Sotriffer, 2018 ) in particular with SARS-CoV-2 main protease. ( Liu et al, 2020 ; Paul et al, 2020 ) Despite covalent inhibition approaches are less studied because the requirement of a nucleophilic residue is a structural limitation and they can be considered as harmful, the resurgence of covalent drugs encourage to also consider covalent inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…( Gentile et al, 2020 ; Ngo et al, 2020 ) A strategy of achieving irreversible inhibition of this protease has also been addressed by the design of compounds to create a covalent bond with the cysteine 145 residue (Cys145) of the catalytic dyad. (Pillaiyar, et al, 2020) While classical docking studies are widely reported in the literature,( Kitchen et al, 2004 ) docking studies for covalent protein inhibition are less common,( Kumalo et al, 2015 ; Sotriffer, 2018 ) in particular with SARS-CoV-2 main protease. ( Liu et al, 2020 ; Paul et al, 2020 ) Despite covalent inhibition approaches are less studied because the requirement of a nucleophilic residue is a structural limitation and they can be considered as harmful, the resurgence of covalent drugs encourage to also consider covalent inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D structure of a molecule is determined not only by its basic structural network, which is defined by covalent bonding, but also by noncovalent interactions. Intricate noncovalent interactions govern many areas of biology and chemistry, including the design of new materials and drugs . Weak noncovalent interactions encompass hydrogen bonding, dipole–dipole interactions, steric repulsion, and London dispersion forces.…”
Section: Introductionmentioning
confidence: 99%
“…They all have potential to form C-S (Cys145) covalent bond leading to irreversible covalent inhibitors. Covalent inhibitors have been approved as drugs by FDA since a decadereversing the trend of disallowing it with a fear of toxic effects (Awoonor-Williams et al, 2017;Sotriffer, 2018;Ghosh et al, 2019). Several advantages of the covalent drugs have encouraged its designing in the present time.…”
Section: Non-covalent Dockingmentioning
confidence: 99%